2023
DOI: 10.1128/spectrum.00696-23
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Type 4B Secretion System Substrates That Are Conserved among Coxiella burnetii Genomes and Promote Intracellular Growth

Abstract: Coxiella burnetii secretes effector proteins via a T4BSS that are required for successful infection. Over 150 C. burnetii proteins are reported to be T4BSS substrates and often by default considered putative effectors, but few have assigned functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Its expression is regulated by a PmrA promoter and it includes a putative C-terminal E-Block secretion signal(17). CBU2007 has been recently validated as a secreted C. burnetii effector protein conserved among C. burnetii genomes(18), is important for CCV biogenesis(18) and essential for C. burnetii survival in primary macrophages(19). Nested PCR followed by sequencing(20) indicated that the transposon insertion occurred 711 bp downstream of the gene starting codon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its expression is regulated by a PmrA promoter and it includes a putative C-terminal E-Block secretion signal(17). CBU2007 has been recently validated as a secreted C. burnetii effector protein conserved among C. burnetii genomes(18), is important for CCV biogenesis(18) and essential for C. burnetii survival in primary macrophages(19). Nested PCR followed by sequencing(20) indicated that the transposon insertion occurred 711 bp downstream of the gene starting codon.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic screen of a library of C. burnetii mutants carrying transposon insertions in genes encoding predicted and validated effector proteins allowed us to pinpoint a transposon insertion in cbu2007 , which largely inhibited LBPA localization at CCVs. CBU2007 is the highest-scoring predicted effector by the S4TE algorithm(16) and has been recently validated as a C. burnetii effector protein(18). CBU2007 is required for intracellular replication(18) and, more importantly, is essential for survival in primary macrophages and virulence in mice(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation